3-D NUMERICAL INVESTIGATION AND OPTIMIZATION OF CENTRIFUGAL SLURRY PUMP USING COMPUTATIONAL FLUID DYNAMICS - Cellek, Mehmet Salih; Engin, Tahsin (TURKISH SOC THERMAL SCIENCES TECHNOLOGY, 2016)
Energy conversion applications are directly affected through the employment of turbomachines and their efficiencies. Energy importance and wide-spread application of turbomachines, make it crucial to optimize their components. In order to optimizastion, the actual flow field and the interaction between the components must be revealed as 3-D studies. Although many studies have focused on the component optimization, mainly volute and impeller in water pumps, there is no systematic elaboration of the same methodology for centrifugal slurry pumps. The purpose of this paper is to improve the performance of a centrifugal slurry pump by means of Computational Fluid Dynamics (CFD). Therefore, an extensive parametric study has been carried out in order to optimize the shroud type impeller taking into account the blade discharge angle (beta(2)), addition splitter blades and modified blade (backward long blades). Additionally, the tongue region of the original pump is re-designed. The results obtained in this study show that it is possible to improve the performance of the impeller and the volute of the centrifugal slurry pump by choosing correct parameters. From the analysis point of view, it is demonstrated numerically that the hydraulic efficiency of the centrifugal slurry pump can be increased up to 9% by using the backward long blades in addition to modified volute compared to the original ones. The last stage of the study focuses on the performance of slurry pump while handling slurry mixture at different concentrations in comparison with clear water as a case study. The flow pattern is visualized with the instantaneous pressure contours and the velocity streamlines. Furthermore, the characteristic performance curves of each pump are compared and discussed. The numerical solutions of the discredited three-dimensional, incompressible Navier-Stokes equations over the structured mesh are accomplished with commercial software Fluent.
Keywords: Slurry pump; Blade angle; Splitter blade; Parametric study; Optimization; PERFORMANCE-CHARACTERISTICS; SIMULATION; IMPELLERS; FLOW; Thermodynamics; Engineering